Inhibitory Effect of Enterococcus faecium WB2000 on Volatile Sulfur Compound Production by Porphyromonas gingivalis - Nao Suzuki; Takuya Higuchi; Masato Nakajima; Akie Fujimoto; Hiromitsu Morita; Masahiro Yoneda; Takashi Hanioka; Takao Hirofuji (Hindawi Limited, 2016)
Volatile sulfur compounds (VSCs) produced by oral anaerobes are the major compounds responsible for oral malodor. Enterococcus faecium WB2000 is recognized as an antiplaque probiotic bacterium. In this study, the effect of E. faecium WB2000 on VSC production by Porphyromonas gingivalis was evaluated, and the mechanism of inhibition of oral malodor was investigated. P. gingivalis ATCC 33277 was cultured in the presence of four lactic acid bacteria, including E. faecium WB2000. Subsequently, P. gingivalis ATCC 33277, W50, W83, and two clinical isolates were cultured in the presence or absence of E. faecium WB2000, and the emission of VSCs from spent culture medium was measured by gas chromatography. The number of P. gingivalis ATCC 33277 in mixed culture with E. faecium WB2000 decreased at 6 h, and the rate of decrease was higher than that in mixed cultures with the other lactic acid bacteria. The numbers of five P. gingivalis strains decreased at similar rates in mixed culture with E. faecium WB2000. The concentration of methyl mercaptan was lower in spent culture medium from P. gingivalis and E. faecium WB2000 cultures compared with that from P. gingivalis alone. Therefore, E. faecium WB2000 may reduce oral malodor by inhibiting the growth of P. gingivalis and neutralizing methyl mercaptan.